2017
DOI: 10.1002/ajhb.23073
|View full text |Cite
|
Sign up to set email alerts
|

Stress, sex, and plague: Patterns of developmental stress and survival in pre‐ and post‐Black Death London

Abstract: Objectives: Previous research revealed declines in survivorship in London before the Black Death (c. 1346Death (c. -1353, and improvements in survivorship following the epidemic. These trends indicate that there were declines in general levels of health before the Black Death and improvements thereof afterwards. This study expands on previous research by examining whether changes in survivorship were consistent between the sexes, and how patterns of developmental stress markers changed before and after the Bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 98 publications
(112 reference statements)
1
17
0
Order By: Relevance
“…Analyses from before, during, and after the Black Death in Denmark showed that urbanization had differential impacts on survivorship across the lifespan (Kelmelis & DeWitte, 2021 ). Further, despite potential sex differences following the pandemic (e.g., DeWitte, 2018 ; DeWitte & Lewis, 2021 ), research on whether sex was associated with previous stress, frailty, and thus mortality risks during the Black Death and subsequent recurring plagues has produced mixed results (Curtis & Roosen, 2017 ; DeWitte, 2009 , 2010 ; Godde, Pasillas, & Sanchez, 2020 ).…”
Section: Anthropological Approaches To Infectious Diseasementioning
confidence: 99%
“…Analyses from before, during, and after the Black Death in Denmark showed that urbanization had differential impacts on survivorship across the lifespan (Kelmelis & DeWitte, 2021 ). Further, despite potential sex differences following the pandemic (e.g., DeWitte, 2018 ; DeWitte & Lewis, 2021 ), research on whether sex was associated with previous stress, frailty, and thus mortality risks during the Black Death and subsequent recurring plagues has produced mixed results (Curtis & Roosen, 2017 ; DeWitte, 2009 , 2010 ; Godde, Pasillas, & Sanchez, 2020 ).…”
Section: Anthropological Approaches To Infectious Diseasementioning
confidence: 99%
“…Ice Age (Brooke, 2014;Campbell, 2016). Bioarchaeological research in London has examined how severe famine events produced by environmental changes-in syndemic interaction with intense population pressures, increasing urbanization, and dramatic social inequalitymight have exacerbated vulnerability to plague, leading to higher mortality rates than might have otherwise been the case (DeWitte, 2015b(DeWitte, , 2018(DeWitte, , 2021DeWitte & Slavin, 2013; see also Section 9.1). Associations have also been suggested between climate conditions and other historical pandemics, such as the Antonine Plague in the second century CE (Elliott, 2016) and the Plague of Justinian (also referred to as the First Pandemic of Plague) that began in the sixth century CE (Harper, 2017;McCormick et al, 2012, see also .…”
Section: Cultural Resilience Figures Heavily In Temple Andmentioning
confidence: 99%
“…As a final point of discussion, bioarchaeologists engaging with life-course approaches and considering the relationship between skeletal lesions representing early life stresses and adult disease and mortality (e.g., DOHaD) might view the results of this study as an example of the powerful influence of social forces on selective mortality. The possibility that long-term health outcomes and risk of death may have social-not just developmental-origins (DeWitte, 2018;DeWitte et al, 2016;Gowland, 2015;Temple, 2019)…”
Section: Wisementioning
confidence: 99%